Estimation of the epidemiological impact of the organized screening program for colorectal cancer. (13th November 2019) - Barre, S; Leleu, H; Taleb, S; Vimont, A
Abstract: Introduction: Colorectal cancer (CRC) is the third most common cancer and the second most deadly in France. A CRC national organized screening (OS) program was set up in France in 2009. It targets asymptomatic people aged 50 to 74 year with medium risk of CRC. OS program is based on fecal immunochemical test (FIT) followed by colonoscopy. Participation rate over the last period showed a participation rate of 34%, far from the European standards and the 45% target objective of the French cancer plan. Methods: The epidemiological impact of the DO-CCR was estimated from the results of an individual simulation model adapted from the MISCAN-Colon model, calibrated and transposed to the French context. The model simulates the natural history of CRC in a cohort of 5, 000, 000 individuals from birth to death. The simulated population reproduced the age and sex structure of the French population. Current screening strategy was simulated for the entire population. A first analysis was conducted to estimate the individual impact of screening by sex and by age of screening initiation and cessation. A second analysis was carried out to estimate the global impact of the based on various participation rates. Results: FIT every 2 years, from the age of 50, is associated with a reduction in the CRC incidence of 21% for women and 24% for men and a reduction in CRC mortality of 43% for women and 51% for men. At the current level of participation, the OS reduces incidence by 5% and mortality by 14% (2, 200 CCR and 2, 600 deaths per year) compared to no OS. The impact would be reduced by an additional 3% and 8% for participation rates of 45% and 65% respectively, a decrease of 1, 300 and 3, 500 cases per additional year. Similarly, mortality would decrease by an additional 8% and 22% for participation rates of 45% and 65%, respectively additional decreases of 1, 400 and 4, 000 deaths per year. Key messages: These results confirm that in a population at medium risk for CRC, the OS is an effective strategy for reducing incidence of CRC. Increasing participation rate to reach the Cancer Plan's objectives remains a key issue in France.